Superhard and superconducting B6C. (December 2017) - Xia, Kang; Ma, Mengdong; Liu, Cong; Gao, Hao; Chen, Qun; He, Julong; Sun, Jian; Wang, Hui-Tian; Tian, Yongjun; Xing, Dingyu
Abstract: Crystal structure searching and ab initio calculations have been used here to explore low-energy structures of boron carbides under high pressure. Under pressures of 85–110 GPa, a metastable B6 C with R 3 ¯ m symmetry is found to be energetically more stable than the mixture of previous B4 C and elemental boron. This B6 C is a rhombohedral structure and contains mooncake-like B24 clusters with stuffing of C2 pairs. The mechanical and dynamical stabilities of this structure at ambient pressure are confirmed by its elastic constants and phonon dispersions. The bulk modulus and shear modulus of this newly predicted B6 C at ambient pressure reach high values of 291 GPa and 272 GPa, respectively. The Vickers hardness is calculated to be around 48 GPa, and its melting temperature at ambient pressure is estimated to be around 2500 K, indicating that this metastable B6 C is a potential superhard material with very good thermal stability. Interestingly, this superhard B6 C structure is also found to be superconducting and its superconducting critical temperature ( T c ) is evaluated to be around 12.5 K at ambient pressure by electron-phonon coupling. Graphical abstract: Highlights: A new B6 C phase is found to be energetically and dynamically stable at high pressure and metastable at ambient condition. This B6 C structure is a potential superhard material and its Vickers hardness is calculated to be around 48 GPa. This B6 C structure has very good thermal stability and its melting temperature is estimated to be around 2500 K. This B6 C structure is found to be superconducting at ambient pressure and its Tc is estimated to be about 12.5 K. This B6 C structure is predicted to be a multifunctional material and may have potential applications value.